AKTIVITAS SISWA KELAS AKSELERASI SMP NEGERI 1 SIDOARJO MENJELANG SUMATIF AKHIR SEMESTER PADA MATA PELAJARAN IPA - Mulyaningrum, Harnis Sekar; Erman, Erman; Ilhami, Fasih Bintang (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2024)
The purpose of this study is to explain the activities of accelerated class students and students who get the highest, medium, and lowest grades before the odd End of Semester Summative in science subjects. The type of research used is qualitative descriptive. This research involved targets, namely accelerated class students and 1 science teacher of JHS State of 1 Sidoarjo. The research instruments used were student response questionnaires, student response interviews, and teachers. The results showed that accelerated class student activities, namely learning carried out by 33 students, learning every day by 20 students, following tutoring by 21 students, studying with friends by 16 students, making a study schedule for 19 students, exercising by 4 students, participating in extracurricular activities by 7 students, participating in extracurricular activities outside school by 11 students, breakfast before the exam by 25 students,Â  33 students are in good physical condition, and 20 students are in a happy emotional state. The activities of accelerated class students who get the highest scores are not too dense. The activity of accelerated class students who get moderate grades is denser than students who get the highest grades. The activities of accelerated class students who get the lowest grades are not as dense as students who get the highest and lowest scores.